The Opportunities and Challenges of Integrating Hologram Experiments into a Highly Visual Telepresence Course - Matere, I.; Weng, C.; Chien-Yu, C.; Chi-Hao, C. (Jurnal Pendidikan IPA Indonesia, 2021)
Higher education is used to nurture advanced specialized training; however, nurturing innovative and practical ability is hard to put into practice. In experimental teaching, hands-on activities are offered to promote students’ practical ability, leading to better-specialized training. This study aims to explore students’ engagement, communication and collaborative skills, as well as learning outcomes by integrating hologram experiments into a university course. Eight university students participated in this study for 3-weeks. Hologram theory was taught in the first week, while in the second and third weeks, the students performed experiments. Pre- and post-test data were collected using questionnaires during the first and last week, respectively. Besides, in-depth interviews were conducted. The findings revealed that students were able to interact with each other, which promoted their engagement in experimenting. Moreover, teammates were able to communicate and collaborate effectively, which led to higher achievement in their learning outcomes. Despite the benefits reported, opportunities and challenges were identified for teachers and students to be aware of during hologram experiments to help them develop creative skills and develop an understanding of holography concepts.